Monocytic Cell Activation by Nonendotoxic Glycoprotein from Prevotella intermedia ATCC 25611 Is Mediated by Toll-Like Receptor 2 - Sugawara, Shunji (American Society for Microbiology, 2001)
Lipopolysaccharide (LPS) preparations from gram-negative black-pigmented bacteria such as Porphyromonas gingivalis and Prevotella intermedia activate cells from non-LPS-responsive C3H/HeJ mice, but it is still unclear whether this activity is due to the unique structure of LPS or to a minor component(s) responsible for the activity in the preparation. A nonendotoxic glycoprotein with bioactivity against cells from C3H/HeJ mice was purified from a hot phenol-water extract of P. intermedia ATCC 25611 and designated Prevotella glycoprotein (PGP). Treatment of human monocytic THP-1 cells with 22-oxyacalcitriol (OCT) induced maturation and marked expression of CD14 on the cells, but the cells constitutively expressed Toll-like receptor 2 (TLR2) and TLR4 on the cells irrespective of the treatment. PGP induced a high level of interleukin-8 production at doses of 100 ng/ml and higher in OCT-treated THP-1 cells compared with Salmonella LPS, and the production was significantly inhibited by anti-CD14 and anti-TLR2 but not anti-TLR4 antibodies. Consistent with this, TLR2-deficient murine macrophages did not respond to PGP. It was also shown that PGP activity on the THP-1 cells was LPS-binding protein dependent and was inhibited by a synthetic lipid A precursor IV(A). These results indicate that PGP activates monocytic cells in a CD14- and TLR2-dependent manner.